High-performance chloride-doped polyaniline activated carbon modified with PluronicTM template for electrochemical desalination - Oliveira, Kaíque Souza Gonçalves Cordeiro (Universidade Federal de São Carlos, 2023)
Activated carbon obtained from chloride-doped polyaniline (PAC/Cl) is an attractive material for brackish water desalination using capacitive deionization (CDI), due to its easy synthesis, low cost, and fast electrosorption kinetics. However, its low content of surface oxygen groups (SOGs) suppresses the salt adsorption capacity (SAC), despite high specific surface area. In this thesis, different strategies to improve the SAC and boost the kinetics of PAC/Cl electrodes were investigated by modifying the synthesis procedure. Firstly, the use of PluronicTM F127 (PLR) as a template (CTAK electrode) allowed modification of the structure and textural properties of the carbonized and activated samples, increasing the SOG content by 26% (from 4.2 to 5.3 at.%), compared to the electrode prepared in the absence of PLR (CTAK*). Consequently, the electrode hydrophobicity was reduced by 2.1-fold (from 87.4 to 40.9º) and the desalination performance was enhanced, especially using an asymmetric electrode configuration (SAC enhancement from 11.4 to 21.0 mg g-1). Despite the slower kinetics observed using CTAK, compared to CTAK*, when the SAC and electrosorption/desorption kinetics were considered together, CTAK outperformed CTAK* by ~1.7-fold (from 932 to 1560 mg g-1 day-1), in both symmetric and asymmetric configurations. As a second approach, the use of PLR combined with hydrothermal carbonization, despite leading to a 3D hierarchical framework, hindered the access to the pores, negatively impacting the process kinetics. The results showed that the use of PLR-modified PAC/Cl is a simple and effective strategy for obtaining low-cost activated carbons with distinct surface chemistry that can improve desalination performance.
Carvão ativado de alto desempenho de polianilina dopada com cloreto modificada com template PluronicTM para dessalinização eletroquímica
Keywords: Capacitive deionization; Polyaniline activated carbon; Surface functional groups; PluronicTM templating agent; Hydrothermal carbonization; Deionização capacitiva; Carvão ativado de polianilina; Grupos funcionais de superfície; Agente template PluronicTM; Carbonização hidrotérmica; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA